Diethylstilbestrol exposure disrupts mouse oocyte meiotic maturation in vitro through affecting spindle assembly and chromosome alignment. (June 2020) - Ding, Zhi-Ming; Hua, Li-Ping; Ahmad, Muhammad Jamil; Safdar, Muhammad; Chen, Fan; Wang, Yong-Shang; Zhang, Shou-Xin; Miao, Yi-Liang; Xiong, Jia-Jun; Huo, Li-Jun
Abstract: An adverse tendency induced by the environmental estrogens in female reproductive health is one serious problem worldwide. Diethylstilbestrol (DES), as a synthetic estrogen, is still used as an animal growth stimulant in terrestrial livestock and aquaculture illegally. It has been reported to negatively affect ovarian function and oogenesis. Nevertheless, the mechanism and toxicity of DES on oocyte meiotic maturation are largely unknown. Herein, we found that DES (40 μM) intervened in mouse oocyte maturation and first polar body extrusion (PBE) was decreased in vitro. Cell cycle analysis showed meiotic process was disturbed with oocytes arrested at metaphase I (MI) stage after DES exposure. Further study showed that DES exposure disrupted the spindle assembly and chromosome alignment, which then continuously provoke the spindle assemble checkpoint (SAC). We also observed that the acetylation levels of α-tubulin were dramatically increased in DES-treated oocytes. In addition, the dynamics of actin were also affected. Moreover, the distribution patterns of estrogen receptor α (ERα) were altered in DES-treated oocyte, as indicated by the significant signals accumulation in the spindle area. However, ERα inhibitor failed to rescue the defects of oocyte maturation caused by DES. Of note, the same phenomenon was observed in estrogen-treated oocytes. Collectively, we showed that DES exposure lead to the oocyte meiotic failure via impairing the spindle assembly and chromosome alignment. Our research is helpful to understand how environmental estrogen affects female germ cells and contribute to design the potential therapies to preserve fertility especially for occupational exposure. Highlights: DES exposure caused the failure of first polar body extrusion in mouse oocytes and disturbed cell cycle process. DES exposure disturbed the cytoskeletal dynamic and chromosome alignment. DES exposure increased acetylation level of α-tubulin. DES exposure continuously activated the spindle assembly checkpoint. DES exposure changed the distribution pattern of estrogen receptor α.